Effect of assistive devices on the precision of digital impressions for implants placed in edentulous maxilla: an in vitro study - Rena Masu; Shinpei Tanaka; Minoru Sanda; Keita Miyoshi; Kazuyoshi Baba (SpringerOpen, 2021)
Abstract Purpose To examine the effect of assistive devices on the precision of digital impression for multiple implants placed in the edentulous maxilla. Methods A reference model representing an edentulous maxilla with four implants was developed. The digital impression group included three settings: Type 0, without an assistive device; Type 1, with an assistive device connecting only neighboring implants; and Type 2, with an assistive device connecting not only neighboring implants but also the two posterior implants, with perpendicular branches from this bar towards the anterior implants. Digital impressions were made five times for each type using three intraoral scanners (IOSs). For conventional method, silicone impressions and verification jigs were prepared; fabricated plaster models were scanned using a laboratory scanner/industrial 3D scanner. In analysis 1, two-way ANOVA analyzed the effect of IOSs and assistive devices on the precision of digital impressions. In analysis 2, one-way ANOVA compared the silicone impressions, the verification jigs, and the most precise group of digital impressions from analysis 1. Results In analysis 1, the IOS and assistive device type (F = 25.22, p < .0001) effects and the interaction between these two factors (F = 5.64, p = .0005) were statistically significant. In analysis 2, CON, VJ, and digital impression with Type 2 devices (most precise devices in analysis 1) were compared; better precision was obtained by digital impression with Type 2 device than by CON and VJ (F = 30.08, p < .0001). Conclusions For implants placed in an edentulous maxilla, digital impressions with assistive devices can provide better precision compared to silicone impressions and verification jigs.